The effect of different irrigants and intra canal dressing on sinus tract closure - Eshagh ali Saberi; Narges Farhadmollashahi; Elnaz Mousavi (Babol University of Medical Sciences, 2015)
Introduction: antimicrobial activity of irrigants and interappointment intracanal dressing is an important consideration in endodontics . The aim of this study was to evaluate the clinical efficacy of chemomechanical preparation of the necrotic canals with different irrigants and intra canal dressing in the control of root canal infection and sinus tract closure. Materials &Methods: In this study, 65 patients with sinus tract were treated. They were randomly divided into 4 groups. Sodium hypochlorite (NaOCl) and chlorhexidine (CHX) was used as the irrigation solutions in the group one and two, then the canals were filled. In group three, after irrigation with NaOCl, Ca (OH) 2/sterile Saline was used as intra canal medicament, and similar to group three Ca (OH) 2/CHX was used in group four after irrigating by CHX. After 7 days, the intra canal paste was removed and the canals were filled. The sinus tract closure was followed up within 7, 14, and 21-day intervals. The data were analyzed using Chi Square and Kruskal-Wallis statistical tests. Results: The highest mean time of sinus tract closure was for Ca (OH)2/sterile Saline and the lowest was for Ca(OH)2/CHX . The differences of sinus tract closure between group 2&4 (p=0.04), group 3&4 (p=0.004) . Groups were statistically significant. Conclusion: It was concluded that Ca (OH)2/CHX paste as intra canal dressing has good clinical efficacy in the control of root canal infection and sinus tract closure.